Três Obras de Álvaro Siza em Leça da Palmeira: Projeto, Reabilitação, Manutenção - Frederico Antunes de Azevedo Afonso Barbosa (2020)
This integrated master's dissertation focuses on the study of three works by Álvaro Siza in Leça da Palmeira - the Boa Nova Tearoom-Restaurant (1958-1963), the Quinta da Conceição Swimming Pool (1958-1965) and the Swimming Pool in Leça da Palmeira (19601973) - analyzing its entire 'life cycle' over time: design, rehabilitation and maintenance. The three works, part of a Leça de Palmeira tourist appreciation plan, were built between 1958 and 1973, at an early stage in Siza's career. Despite the temporal proximity, the works reveal a conceptual and tectonic evolution in the architect's path, towards the affirmation of an abstract language and the application of 'modern' materials and technologies. The selected projects are also the object of recent rehabilitation works by Álvaro Siza himself, who thus not only has the opportunity to apply his principles in the intervention on pre-existences - respecting the integrity of the work -, but also to contribute to the conservation and enhancement of the works. In the current context of diminishing economic and environmental resources, this work also highlights the importance of implementing preventive strategies and continued maintenance over time - through proposals for future maintenance and correct use - thus contributing to the proper functioning and preservation of integrity and authenticity of the works. The dissertation poses the problem of preserving 20th century architecture, which, being a recent heritage, is often vulnerable because it isn't recognized either by the safeguarding and protection organizations or by the general public. Finally, the work presents contributions to a broader project financed by the Getty Foundation - "Keeping It Modern: Piscina de Marés" - directed towards the elaboration of a management and conservation plan for this work, but also for its framing and perspectives in the candidacy of a set of works by Álvaro Siza for the list of World Heritage.